An automated process for supporting decisions in clustering-based data analysis. (June 2022) - Bernabé-Díaz, José Antonio; Franco, Manuel; Vivo, Juana-María; Quesada-Martínez, Manuel; Fernández-Breis, Jesualdo T.
Highlights: Our approach analyzes the reliability of clusters generated on quantitative metrics. We use statistical properties: stability and goodness of classifications. Our method helps to select the most useful metrics for analyzing the datasets. Our method permits to account for the heterogeneity in datasets. The usefulness of our approach is illustrated in three use cases. Abstract: Background and objective: Metrics are commonly used by biomedical researchers and practitioners to measure and evaluate properties of individuals, instruments, models, methods, or datasets. Due to the lack of a standardized validation procedure for a metric, it is assumed that if a metric is appropriate for analyzing a dataset in a certain domain, then it will be appropriate for other datasets in the same domain. However, such generalizability cannot be taken for granted, since the behavior of a metric can vary in different scenarios. The study of such behavior of a metric is the objective of this paper, since it would allow for assessing its reliability before drawing any conclusion about biomedical datasets. Methods: We present a method to support in evaluating the behavior of quantitative metrics on datasets. Our approach assesses a metric by using clustering-based data analysis, and enhancing the decision-making process in the optimal classification. Our method assesses the metrics by applying two important criteria of the unsupervised classification validation that are calculated on the clusterings generated by the metric, namely stability and goodness of the clusters. The application of our method is facilitated to biomedical researchers by our evaluomeR tool. Results: The analytical power of our methods is shown in the results of the application of our method to analyze (1) the behavior of the impact factor metric for a series of journal categories; (2) which structural metrics provide a better partitioning of the content of a repository of biomedical ontologies, and (3) the heterogeneity sources in effect size metrics of biomedical primary studies. Conclusions: The use of statistical properties such as stability and goodness of classifications allows for a useful analysis of the behavior of quantitative metrics, which can be used for supporting decisions about which metrics to apply on a certain dataset.